ANALISA KUANTITAS SISTEM PROSES PEMBUATAN ES KRIM BERBAHAN TAMBAHAN TEPUNG TEMPE KEDELAI - Ali Zainal Abidin Alaydrus (Journal of Scientech Research and Development, 2022)
This study aims to determine the best composition of tempe flour additives, in ice cream processing to determine the mass balance in this processing, physical properties (viscosity, overrun, melting time, and total solids), chemical properties (fat and protein content). ), and organoleptic flavor of ice cream from tempeh flour. The research method uses empirical methods with variations in the mixture of ingredients from 2 (two) factors to get the best proportions. Where the first factor is the proportion of tempe flour with 3 (three) levels (5, 7.5, and 10%) and the second factor is the proportion of carrageenan with 2 (two) levels (0.5 and 1%). The results of physical and chemical analysis compared with commercial ice cream products, SNI and organolaptics are the best response recommended for mass production. The results showed that the treatment with variations in the proportions of carrageenan and tempeh flour had an effect on total solids, fat and protein content, viscosity, overrun, and melting time. Ice cream with the best treatment based on physical and chemical properties found in ice cream with 1% carrageenan and 10% tempe flour containing 32.22% total solids, 5.486% protein, 7.91% fat, 5.23 Pa.s viscosity, overrun 22.132% and 38.667 minutes melting rate. Ice cream with the best treatment based on organoleptic results was found in ice cream with a composition of 0.5% carrageenan and 5% tempeh flour which contained 19.22% total solids, 4.261% protein, 5.031% fat, 2.33 Pa.s dough viscosity, overrun 14.014%, and melting time 30.201 minutes.